Modulated Electrohyperthermia: A New Hope for Cancer Patients. (16th November 2020) - Alshaibi, Huda F.; Al-shehri, Bashayr; Hassan, Basmah; Al-zahrani, Raghad; Assiss, Taghreed
Abstract : According to the World Health Organization, the prevalence of cancer has increased worldwide. Oncological hyperthermia is a group of methods that overheat the malignant tissues locally or systematically. Nevertheless, hyperthermia is not widely accepted, primarily because of the lack of selectivity for cancer cells and because the temperature-triggered higher blood flow increases the nutrient supply to the tumor, raising the risk of metastases. These problems with classical hyperthermia led to the development of modulated electrohyperthermia (mEHT). The biophysical differences of the cancer cells and their healthy hosts allow for selective energy absorption on the membrane rafts of the plasma membrane of the tumor cells, triggering immunogenic cell death. Currently, this method is used in only 34 countries. The effectiveness of conventional oncotherapies increases when it is applied in combination with mEHT. In silico, in vitro, and in vivo preclinical research studies have all shown the extraordinary ability of mEHT to kill malignant cells. Clinical applications have improved the quality of life and the survival of patients. For these reasons, many other research studies are presently in progress worldwide. Thus, the objective of this review is to highlight the capabilities and advantages of mEHT and provide new hopes for cancer patients worldwide.